CONDITION FACTOR AND SIZE VARIATION OF CATFISH FRY REARING IN A SUPER-INTENSIVE UFBs-RAS SYSTEM: KONDISI FAKTOR DAN KERAGAMAN UKURAN BENIH IKAN LELE PADA PEMELIHARAAN SUPER INTENSIF DALAM SISTEM UFBs-RAS - Subhan, Ujang; Afriza, Azka Reyza; Maulina, Ine; Herman, Roffi Grandiosa (Fakultas Perikanan dan Ilmu Kelautan, IPB University, 2025)
Catfish (Clarias gariepinus) is one of the leading aquaculture commodities in Indonesia, with a production volume reaching 1.01 million tons, accounting for approximately 15% of the national aquaculture output in 2020. The availability of high-quality fry is crucial for the sustainability of catfish farming. This study aims to evaluate the effect of high stocking densities on survival rate, condition factor, and size variation of catfish fry reared in UFBs-RAS. This research was conducted at PUI-PT Nano Powder Functional Universitas Padjadjaran (Jatinangor) from October to November 2023. The study tested catfish fry with lengths of 3–4 cm and weights of 1.2–1.4 g with four densities (10 fish/L, 15 fish/L, 20 fish/L, 25 fish/L). The results indicated that stocking density did not significantly affect the survival rate (P>0.05), but it did have a significant effect on length and weight variation (P<0.05). The condition factor did not show significant differences (P>0.05) between stocking density treatments. Overall, a density of 25 fish/L yielded the best performance within the UFBs-RAS. Therefore, this density is recommended as the optimal stocking rate for catfish fry rearing in this system. These findings suggest that the application of the UFBs-RAS system provides a strategic solution for the aquaculture industry to enhance the efficiency of catfish fry rearing at high stocking densities while maintaining optimal water quality and growth performance, thereby supporting productivity and sustainability in intensive aquaculture systems.